Analysis of Indoor Air Microflora of Some Daycare Centres in Ilorin South Local Government Area, Nigeria - Sule, I.O.; Agbabiaka, T.O.; Saliu, B.K.; Odebisi-Omokanye, M.B.; Zakariyah, R.F.; Ali, A.A. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2017)
The microflora of air in ten daycare centres within Ilorin South Local Government Area of Kwara State, Nigeria wasinvestigated by settling plate technique. The plates were exposed for a period of 10 minutes at each sampling point. Thecounts of bacteria, total coliform and fungi ranged from 10 to 200, 10 to 170 and 6 to 110 cfu/10 minutes respectively. A totalof 23 microorganisms comprising 12 bacteria and 11 fungi were isolated in this study. These bacteria were Micrococcus sp.,Staphylococcus arlettae, Corynebacterium pseudotuberculosis, Staphylococcus haemolyticus, Corynebacterium kutscheri,Staphylococcus warneri, Staphylococcus aureus, Corynebacterium diphtheriae., Corynebacterium amycolatum, Bacilluspumilus, Corynebacterium matruchotii and Listeria grayi while the fungi were Aspergillus fumigatus, Aspergillus niger,Penicillium chrysogenum, Penicillium sp., Aspergillus flavus, Rhizopus stolonifer, Fusarium oxysporum, Saccharomycescerevisiae, Alternaria alternata, Aspergillus glaucus and Polyporus sp. The predominant bacterium and fungus in this studywere Micrococcus sp. and Aspergillus fumigatus respectively. It can be concluded that the indoor air of the daycare centresused for this study had diverse species of Gram positive bacteria, high occurrence of non-pathogenic bacteria and fungi.Moulds dominate the fungal isolates and some of the bacterial species are commensals found on human body whereas thefungi are environmental in origin. A few pathogenic species were isolated among the bacteria and fungi.